Cover Feature: A Fast, Low‐Temperature Synthesis Method for Hexagonal YMnO3: Kinetics, Purity, Size and Shape as Studied by In Situ X‐ray Diffraction (Chem. Eur. J. 42/2020). Issue 42 (17th June 2020) - Marshall, Kenneth P.; Blichfeld, Anders B.; Skjærvø, Susanne L.; Grendal, Ola G.; van Beek, Wouter; Selbach, Sverre M.; Grande, Tor; Einarsrud, Mari‐Ann
Abstract : A hydrothermal reaction taking place in a capillary while being monitored using in situ X‐ray diffraction from a synchrotron source is depicted in the cover image. The capillary is locally heated from above, while being penetrated by X‐rays, which are diffracted in cone‐like patterns by the powder within. The zoom on the capillary shows the evolution of crystal structures as hexagonal YMnO3 is formed from Mn2 O3 and Y2 O3 in hydroxide solution. More information can be found in the Full Paper by M.‐A. Einarsrud et al. on page 9330 .